Active energy ray-curable peel-off pressure-sensitive adhesive composition and peel-off pressure-sensitive adhesive sheet

JP7643150B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
JP2021064970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-03-11
Estimated Expiration
2041-04-06

AI Technical Summary

Benefits of technology

【0011】 本発明の活性エネルギー線硬化性剥離型粘着剤組成物は、塗工前においては高温下に長時間晒しても硬化することなく(熱安定性)、粘着シートとする際の基材シートへの塗工性に優れ、更には活性エネルギー線の照射前後において所望の粘着力を有し、特に活性エネルギー線照射後の粘着力は極めて低く糊残りなく剥離できる粘着特性を有する活性エネルギー線硬化性剥離型粘着剤組成物とすることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643150000001
    Figure 0007643150000001
  • Figure 0007643150000002
    Figure 0007643150000002
  • Figure 0007643150000003
    Figure 0007643150000003
Patent Text Reader

Abstract

To provide a solventless type active energy ray curable peelable adhesive composition which is not cured before coating even when exposed to a high temperature for a long time (thermal stability), which is excellent in a coating property to a base material sheet in forming an adhesive sheet, further which has desired adhesive force before and after irradiation of an object with an active energy ray, in particular which has an adhesive property of being peeled off without an adhesive residue because the adhesive force after irradiation with the active energy ray is extremely low, and to provide a peelable adhesive sheet.SOLUTION: An active energy ray curable peelable adhesive composition contains an active energy ray curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray curable compound (B) in which the active energy ray curable composition (X) satisfies all of requirements (α)-(ω). A requirement (α): the active energy ray curable compound (B) contains an urethane (meth)acrylic compound (b), a requirement (β): a content of a solvent in the active energy ray curable composition (X) is less than 1 wt.%, a requirement (γ): a content of a thermal polymerization initiator in the active energy ray curable composition (X) is less than 200 ppm, and a requirement (ω): melt viscosity of the active energy ray curable composition (X) at 100°C is 120 Pa s or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an active energy ray-curable release-type pressure-sensitive adhesive composition and a release-type pressure-sensitive adhesive sheet made using the same, and more particularly to an active energy ray-curable release-type pressure-sensitive adhesive composition and a release-type pressure-sensitive adhesive sheet used in the pressure-sensitive adhesive layer of a release-type pressure-sensitive adhesive sheet for temporary protection during processing of workpieces such as semiconductor wafers, printed circuit boards, processed glass products, metal plates, and plastic plates. [Background technology]

[0002] Conventionally, in processing steps such as fabricating integrated circuits on semiconductor wafers or drilling holes, protective adhesive sheets (peelable adhesive sheets) have been used to temporarily protect the workpiece, i.e., the semiconductor wafer, from contamination or damage.

[0003] As such protective pressure-sensitive adhesive sheets, pressure-sensitive adhesive sheets using emulsion-type acrylic resins whose adhesive strength decreases when heated have been proposed (see, for example, Patent Document 1). In addition, a UV-curable emulsion adhesive has been disclosed that uses an acrylic emulsion polymerized without using an emulsifier (dispersant) and a urethane (meth)acrylate compound that has a self-emulsifying property (see, for example, Patent Document 2). Furthermore, a pressure-sensitive adhesive sheet has been disclosed which has, on a substrate film, a solventless acrylic pressure-sensitive adhesive layer containing an acrylic polymer, an acrylic monomer, and a photopolymerization initiator (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-201263 [Patent Document 2] Japanese Patent Application Laid-Open No. 2012-001615 [Patent Document 3] Japanese Patent Application Laid-Open No. 2004-269796 Summary of the Invention [Problem to be solved by the invention]

[0005] The above-mentioned peel-off adhesive sheets for temporary protection are required to have an appropriate adhesive strength to the workpiece due to factors such as the miniaturization of processing technology and the thinning of workpieces, but when they are peeled off after their protective role has been completed, they are also required to be able to be peeled off with extremely light force without leaving any adhesive residue. Furthermore, in recent years, greenhouse gas emissions have become a problem from the perspective of global environmental pollution, and attempts have been made to mitigate the above-mentioned problems by replacing conventional solvent-based materials with water-based or solvent-free materials.

[0006] However, the technique of Patent Document 1 has problems such as insufficient reduction in adhesive strength due to heating and the surfactant remaining on the wafer surface. Therefore, in Patent Document 2, a self-emulsifying urethane (meth)acrylate was used as an emulsion-type adhesive, thereby making it possible to obtain an adhesive without using a surfactant. However, as in Patent Document 1, the decrease in adhesive strength after curing with active energy rays was insufficient.

[0007] Furthermore, the adhesive sheet of Patent Document 3 is not an adhesive sheet whose adhesive strength is reduced by irradiation with active energy rays, and therefore cannot be applied to processed members that have been miniaturized and thinned.

[0008] Under these circumstances, the present invention aims to provide an active energy ray-curable peel-type pressure-sensitive adhesive composition and a peel-type pressure-sensitive adhesive sheet that, before coating, does not harden even when exposed to high temperatures for a long period of time (thermal stability), has excellent applicability to a substrate sheet when made into a pressure-sensitive adhesive sheet, and further has a desired adhesive strength before and after irradiation with active energy rays, and in particular has adhesive properties such that the adhesive strength after irradiation with active energy rays is extremely low and the composition can be peeled off without leaving any adhesive residue. [Means for solving the problem]

[0009] However, the present inventors have discovered that, when an active energy ray-curable peel-type pressure-sensitive adhesive composition containing an acrylic resin and an active energy ray-curable compound is generally exposed to high temperatures, the thermal polymerization initiator remaining in the acrylic resin decomposes, initiating curing of the active energy ray-curable compound, making it impossible to even heat the composition to the temperature required for hot-melt coating. However, the present inventors have discovered that, by using an active energy ray-curable peel-type pressure-sensitive adhesive composition containing an acrylic resin and an active energy ray-curable compound and adjusting the melt viscosity of the acrylic resin and the amount of remaining thermal polymerization initiator within predetermined ranges, an active energy ray-curable peel-type pressure-sensitive adhesive composition can be obtained that has excellent thermal stability and coatability, and that, when made into a peel-type pressure-sensitive adhesive sheet, has excellent adhesive properties before and after irradiation with active energy rays and excellent contamination resistance after peeling.

[0010] That is, the present invention provides an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), An active energy ray-curable peel-off pressure-sensitive adhesive composition, characterized in that the active energy ray-curable composition (X) satisfies all of the following requirements (α) to (ω): Requirement (α): The active energy ray-curable compound (B) contains a urethane (meth)acrylate compound (b). Requirement (β): The solvent content in the active energy ray-curable composition (X) is less than 1% by weight. Requirement (γ): The content of the thermal polymerization initiator in the active energy ray-curable composition (X) is less than 200 ppm Requirement (ω): The melt viscosity of the active energy ray-curable composition (X) at 100°C is 120 Pa·s or less The present invention also provides a release-type pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer in which the above-mentioned active energy ray-curable release-type pressure-sensitive adhesive composition is crosslinked. [Effects of the Invention]

[0011] The active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention does not harden even when exposed to high temperatures for a long period of time before coating (thermal stability), has excellent applicability to a substrate sheet when made into a pressure-sensitive adhesive sheet, and further has a desired adhesive strength before and after irradiation with active energy rays, and in particular, has extremely low adhesive strength after irradiation with active energy rays, so that the composition can be made into an active energy ray-curable peel-type pressure-sensitive adhesive composition having adhesive properties that allow peeling without leaving any adhesive residue. DETAILED DESCRIPTION OF THE INVENTION

[0012] Hereinafter, embodiments for carrying out the present invention will be specifically described, but the present invention is not limited to these. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively. In the present invention, the term "sheet" is not particularly distinguished from "film" or "tape" and is used to include these terms.

[0013] The active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention is generally used in the pressure-sensitive adhesive layer of a release-type pressure-sensitive adhesive sheet that is intended to be peeled off after being attached to a workpiece such as a metal plate, a plastic plate, a semiconductor wafer, etc. The release-type pressure-sensitive adhesive sheet is obtained by coating the active energy ray-curable release-type pressure-sensitive adhesive composition on a substrate sheet to form a pressure-sensitive adhesive layer, and after being attached to the workpiece, the pressure-sensitive adhesive layer is cured by irradiating it with active energy rays, thereby reducing the adhesive strength and allowing it to be easily peeled off from the workpiece.

[0014] Hereinafter, the active energy ray-curable peelable pressure-sensitive adhesive composition of the present invention will be described. The composition (X) contains an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), The (meth)acrylic resin (A) has a weight average molecular weight of 50,000 or more and 1,000,000 or less and contains a structural unit derived from a functional group-containing monomer, An active energy ray-curable peel-off pressure-sensitive adhesive composition, characterized in that the active energy ray-curable composition (X) satisfies all of the following requirements (α) to (ω): Requirement (α): The active energy ray-curable compound (B) contains a urethane (meth)acrylate compound (b). Requirement (β): The solvent content in the active energy ray-curable composition (X) is less than 1% by weight. Requirement (γ): The content of the thermal polymerization initiator in the active energy ray-curable composition (X) is less than 200 ppm Requirement (ω): The melt viscosity of the active energy ray-curable composition (X) at 100°C is 120 Pa·s or less The following explains each step in order.

[0015] [(Meth)acrylic resin (A)] The (meth)acrylic resin (A) is a resin obtained by polymerizing a polymerization component containing at least one kind of (meth)acrylic monomer, and examples thereof include acrylic resins obtained by polymerizing a polymerization component containing a (meth)acrylic monomer as the main component and, in some cases, various other polymerizable monomers.

[0016] Incidentally, "mainly composed of" a (meth)acrylic monomer means that the (meth)acrylic monomer accounts for typically 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more of the total polymerizable components.

[0017] Examples of the (meth)acrylic monomer include (meth)acrylic acid or a derivative thereof, and (meth)acrylamide or a derivative thereof.

[0018] Examples of the derivatives of (meth)acrylic acid include alkyl group-containing (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.

[0019] Other examples of the derivatives of (meth)acrylic acid include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; biphenyloxy structure-containing (meth)acrylates such as biphenyloxyethyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate. polycyclic (meth)acrylates such as methyl acrylate and dicyclopentanyl (meth)acrylate; alkoxy group- or phenoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, and alkylphenoxypolyethylene glycol (meth)acrylate; and the like.

[0020] Further, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, hydroxyl group-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, and epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether, are also included. Examples of the acrylate include halogen-containing (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; and oxetane group-containing (meth)acrylates such as 3-oxetanylmethyl (meth)acrylate, 3-methyloxetanylmethyl (meth)acrylate, 3-ethyloxetanylmethyl (meth)acrylate, 3-butyloxetanylmethyl (meth)acrylate, and 3-hexyloxetanylmethyl (meth)acrylate.

[0021] Examples of the (meth)acrylamide derivatives include N-alkyl group-containing (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hexyl(meth)acrylamide; N-hydroxyalkyl group-containing (meth)acrylamide derivatives such as N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and N-methylol-N-propane(meth)acrylamide; aminomethyl(meth)acrylamide; N-aminoalkyl group-containing (meth)acrylamide derivatives such as N-methoxymethyl(meth)acrylamide and N-ethoxymethyl(meth)acrylamide; N-mercaptoalkyl group-containing (meth)acrylamide derivatives such as mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide; and heterocycle-containing (meth)acrylamide derivatives such as N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0022] These (meth)acrylic monomers may be used alone or in combination of two or more. Among these (meth)acrylic monomers, alkyl group-containing (meth)acrylates are preferably used. The number of carbon atoms in the alkyl group in the alkyl group-containing (meth)acrylate is usually 1 to 20, preferably 4 to 18, and more preferably 8 to 12. Among them, n-butyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, and n-lauryl methacrylate are preferred because they have a glass transition temperature (Tg) of −30° C. or less when made into homopolymers and can easily reduce melt viscosity.

[0023] Furthermore, the polymerization components constituting the (meth)acrylic resin (A) may contain polymerizable monomers other than (meth)acrylic monomers (hereinafter referred to as "other polymerizable monomers"). Examples of the other polymerizable monomers include unsaturated carboxylic acids such as crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamido-N-glycolic acid, and cinnamic acid; carboxylic acid vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl stearate, and vinyl benzoate; aromatic ring-containing monomers such as styrene and α-methylstyrene; acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyl toluene, vinylpyridine, vinylpyrrolidone, itaconic acid dialkyl esters, fumaric acid dialkyl esters, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethylallyl vinyl ketone. These may be used alone or in combination of two or more.

[0024] The other polymerizable monomers may also include photocrosslinkable monomers, which generate radicals when exposed to light. As the photocrosslinkable monomer, for example, a (meth)acrylate monomer having a benzophenone structure such as 4-acryloyloxybenzophenone, 4-acryloyloxyethoxybenzophenone, 4-acryloyloxy-4'-methoxybenzophenone, 4-acryloyloxyethoxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, 4-acryloyloxyethoxy-4'-bromobenzophenone, 4-methacryloyloxybenzophenone, 4-methacryloyloxyethoxybenzophenone, 4-methacryloyloxy-4'-methoxybenzophenone, 4-methacryloyloxyethoxy-4'-methoxybenzophenone, 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-bromobenzophenone, and mixtures thereof may be used. By using such a photocrosslinkable monomer as a copolymerization component, a photocrosslinkable structural moiety can be formed in the (meth)acrylic resin (A).

[0025] The polymerization components constituting the (meth)acrylic resin (A) preferably contain an alkyl group-containing (meth)acrylate monomer and a functional group-containing monomer. The functional group-containing monomer preferably contains at least one functional group-containing monomer selected from a hydroxyl group-containing monomer and a carboxy group-containing monomer. Of these, a functional group-containing monomer containing a (meth)acryloyl group is preferred. Among these, 2-hydroxyethyl (meth)acrylate and (meth)acrylic acid are particularly preferred.

[0026] The alkyl group-containing (meth)acrylate monomer is contained in an amount of usually 40% by weight or more, preferably 50% by weight or more, more preferably 60% by weight or more, based on the total weight of the polymerizable components of the (meth)acrylic resin (A). The upper limit is usually 100% by weight. The content of the functional group-containing monomer is preferably 0.1 to 40 wt%, more preferably 1 to 35 wt%, and even more preferably 5 to 30 wt%, based on the total weight of the polymer components constituting the (meth)acrylic resin (A). If the content of the functional group-containing monomer is too low, the cohesive strength of the pressure-sensitive adhesive layer formed tends to decrease, and reworkability tends to decrease. Conversely, if the content is too high, the melt viscosity tends to increase and the pot life tends to be shortened.

[0027] The other polymerizable monomers are contained in an amount of usually 0 to 30% by weight, preferably 0 to 20% by weight, based on the total polymerizable components of the (meth)acrylic resin (A). Of the other polymerizable monomers, the photocrosslinkable monomer is preferably contained in an amount of usually 0 to 10% by weight, and more preferably 0 to 5% by weight, based on the total polymerizable components of the (meth)acrylic resin (A).

[0028] [Method for producing (meth)acrylic resin (A)] The polymerization method for the (meth)acrylic resin (A) used in the present invention can be a conventionally known method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. For example, a method in which appropriately selected polymerization components and a thermal polymerization initiator are mixed or dropped into an organic solvent and polymerized under predetermined polymerization conditions can be used. Among these, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is particularly preferred because it allows the stable production of an acrylic resin. An example of a preferred method for producing the (meth)acrylic resin (A) used in the present invention will be described below.

[0029] First, the copolymerization components and a thermal polymerization initiator are mixed or dropped into an organic solvent, and solution polymerization is carried out to obtain an acrylic resin solution.

[0030] (organic solvent) Examples of organic solvents used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. These can be used alone or in combination of two or more. Among these solvents, it is preferable to use an organic solvent having a boiling point of 80°C or less, since this allows for efficient production of a solventless acrylic resin by distilling off the solvent from the acrylic resin solution obtained by solution polymerization.

[0031] Examples of organic solvents having a boiling point of 80°C or lower include hydrocarbon solvents such as n-hexane (67°C), alcohol solvents such as methanol (65°C), ester solvents such as ethyl acetate (77°C) and methyl acetate (54°C), ketone solvents such as methyl ethyl ketone (80°C) and acetone (56°C), diethyl ether (35°C), methylene chloride (40°C), and tetrahydrofuran (66°C). Of these, in terms of versatility and safety, it is preferable to use ethyl acetate, acetone, and methyl acetate, and it is particularly preferable to use ethyl acetate and acetone. The numbers in parentheses following the names of the above organic solvents are the boiling points of the respective organic solvents.

[0032] (thermal polymerization initiator) As the thermal polymerization initiator used in the polymerization reaction, azo-based polymerization initiators and peroxide-based polymerization initiators, which are common radical polymerization initiators, can be used. Examples of azo-based polymerization initiators include 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, (1-phenylethyl)azodiphenylmethane, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), ... ,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), etc., and examples of peroxide polymerization initiators include benzoyl peroxide, di-t-butyl peroxide, cumene hydroperoxide, lauroyl peroxide, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-hexyl peroxyneodecanoate, diisopropyl peroxycarbonate, diisobutyryl peroxide, etc. These can be used alone or in combination of two or more.

[0033] In producing the acrylic resin, it is preferable to use an organic solvent having a boiling point of 80°C or less as a reaction solvent for solution polymerization and carry out polymerization at a relatively low temperature, and if a thermal polymerization initiator with a high 10-hour half-life temperature is used in this case, the thermal polymerization initiator is likely to remain. If the thermal polymerization initiator remains, gelation tends to occur in the step of distilling off the solvent from the acrylic resin solution or in the step of heating to form an active energy ray-curable peel-type pressure-sensitive adhesive composition, which will be described later.

[0034] Therefore, in the present invention, from the viewpoint of stably performing the step of distilling off the solvent from the acrylic resin solution obtained by solution polymerization and the step of heating to obtain an active energy ray-curable peel-type pressure-sensitive adhesive composition, it is preferable to use a thermal polymerization initiator having a 10-hour half-life temperature of 60°C or less among the above thermal polymerization initiators. Among these, 2,2'-azobis(2,4-dimethylvaleronitrile) (52°C), 2,2'-azobis(2-cyclopropylpropionitrile) (49.6°C), 2,2' -azobis(4-methoxy-2,4-dimethylvaleronitrile) (30°C), t-butyl peroxypivalate (54.6°C), t-hexyl peroxypivalate (53.2°C), t-hexyl peroxyneodecanoate (44.5°C), diisopropyl peroxycarbonate (40.5°C), diisobutyryl peroxide (32.7°C), and more preferably 2,2'-azobis(2,4-dimethylvaleronitrile) (52°C) and t-hexyl peroxypivalate (53.2°C). The values ​​in parentheses following each compound name above are the 10-hour half-life temperatures of each compound.

[0035] The amount of the thermal polymerization initiator used is usually 0.001 to 10 parts by weight, preferably 0.1 to 8 parts by weight, particularly preferably 0.5 to 6 parts by weight, even more preferably 1 to 4 parts by weight, especially preferably 1.5 to 3 parts by weight, and most preferably 2 to 2.5 parts by weight, per 100 parts by weight of the polymerization components. If the amount of the thermal polymerization initiator used is too small, the polymerization rate of the acrylic resin tends to decrease, the amount of residual monomer increases, and the weight-average molecular weight of the acrylic resin tends to increase. If the amount used is too large, the time required for the follow-up heating described below will be long, which is not productive.

[0036] (Polymerization conditions, etc.) The solution polymerization may be carried out under conventionally known polymerization conditions. For example, the polymerization components and a thermal polymerization initiator may be mixed or dropped into a solvent, and polymerization may be carried out under predetermined polymerization conditions.

[0037] The polymerization temperature in the above polymerization reaction is usually 40 to 120° C., but in the present invention, from the viewpoint of ensuring a stable reaction, it is preferably 50 to 90° C., particularly preferably 55 to 75° C., and even more preferably 60 to 70° C. If the polymerization temperature is too high, the acrylic resin tends to gel easily, while if it is too low, the activity of the thermal polymerization initiator decreases, which tends to reduce the polymerization rate and increase the amount of residual monomer.

[0038] The polymerization time in the polymerization reaction (the time until the start of the follow-up heating, if follow-up heating is performed as described below) is not particularly limited, but is preferably 0.5 hours or more from the addition of the final thermal polymerization initiator, particularly preferably 1 hour or more, further preferably 2 hours or more, and particularly preferably 5 hours or more. The upper limit of the polymerization time is usually 72 hours. The polymerization reaction is preferably carried out while refluxing the solvent, since this facilitates heat removal.

[0039] In the production of the acrylic resin, it is preferable to thermally decompose the thermal polymerization initiator by follow-up heating in order to reduce the amount of residual thermal radical initiator.

[0040] The drive-in heating temperature is preferably higher than the 10-hour half-life temperature of the thermal polymerization initiator, and specifically is usually 40 to 150°C, preferably 55 to 130°C from the viewpoint of suppressing gelation, and particularly preferably 75 to 95°C. If the drive-in heating temperature is too high, the acrylic resin tends to yellow, while if it is too low, the polymerization components and thermal polymerization initiator remain, and the stability over time and the thermal stability of the acrylic resin tend to decrease. In this way, an acrylic resin solution can be obtained.

[0041] Since the acrylic resin used in the present invention is preferably a solvent-free acrylic resin that does not contain a solvent, the solvent is then distilled off from the acrylic resin solution.

[0042] The step of distilling off the solvent from the acrylic resin solution can be carried out by a known general method. Examples of the method for distilling off the solvent include a method for distilling off the solvent by heating and a method for distilling off the solvent by reducing pressure. However, from the viewpoint of efficiently distilling off the solvent, a method for distilling off the solvent by heating under reduced pressure is preferred.

[0043] When the solvent is distilled off by heating, the temperature is preferably 60 to 150° C., and it is particularly preferable to hold the reaction solution after polymerizing the acrylic resin at 60 to 80° C. to distill off the solvent, and then distill off the solvent at 80 to 150° C., in order to minimize the amount of remaining solvent. Note that, in order to prevent gelation of the acrylic resin, it is preferable not to distill off the solvent at a temperature exceeding 150° C.

[0044] When the solvent is distilled off under reduced pressure, the pressure is preferably 20 to 101.3 kPa, and in particular, it is preferable to maintain the pressure in the range of 50 to 101.3 kPa to distill off the solvent in the reaction solution, and then distill off the remaining solvent at 0 to 50 kPa, in order to minimize the amount of remaining solvent. In this way, the (meth)acrylic resin (A) used in the present invention can be produced.

[0045] [Physical Properties of (Meth)acrylic Resin (A)] The content of the thermal polymerization initiator remaining in the (meth)acrylic resin (A) used in the present invention is usually preferably less than 400 ppm, particularly preferably less than 200 ppm, further preferably less than 100 ppm, and particularly preferably less than 50 ppm. The lower limit is 0 ppm. If this value is too large, the thermal stability during coating tends to decrease. The content of the thermal polymerization initiator is measured by liquid chromatography mass spectrometry (LC-MS). In order to adjust the content of the thermal polymerization initiator to the above amount, it is preferable to thermally decompose the thermal polymerization initiator by follow-up heating.

[0046] [Physical Properties of (Meth)acrylic Resin (A)] The weight-average molecular weight (Mw) of the (meth)acrylic resin (A) obtained as described above is preferably 50,000 or more, more preferably 70,000 to 1,500,000, more preferably 90,000 to 1,000,000, and particularly preferably 100,000 to 500,000. If the weight-average molecular weight is too small, the cohesive strength of the resulting pressure-sensitive adhesive layer tends to decrease, and the adhesive performance and reworkability before curing with active energy rays tend to decrease. On the other hand, if the weight-average molecular weight is too large, the melt viscosity of the acrylic resin tends to increase, and the coatability tends to decrease.

[0047] The dispersity of the (meth)acrylic resin (A) [weight average molecular weight (Mw) / number average molecular weight (Mn)] is preferably 10 or less, more preferably 7 or less. If the dispersity is too high, the cohesive force tends to decrease. The lower limit of the dispersity is usually 1.

[0048] The weight-average molecular weight of the (meth)acrylic resin (A) is the weight-average molecular weight converted to standard polystyrene molecular weight and can be measured using a high-performance liquid chromatograph (manufactured by Japan Waters, "Waters 2695 (main body)" and "Waters 2414 (detector)") with three Shodex GPCKF-806L columns (molecular weight exclusion limit: 2 × 107, separation range: 100 to 2 × 107, theoretical plate number: 10,000 plates / column, packing material: styrene-divinylbenzene copolymer, packing particle size: 10 μm) connected in series. The number-average molecular weight can also be measured in a similar manner. The dispersity can be determined from the measured values ​​of the weight-average molecular weight and number-average molecular weight.

[0049] The melt viscosity of the (meth)acrylic resin (A) used in the present invention at 100°C is less than 1000 Pa·s, preferably 800 to 0.1 Pa·s, and more preferably 500 to 1 Pa·s. If this value is too small, the cohesive strength when formed into an adhesive layer tends to be insufficient, and the adhesive properties before irradiation with active energy rays tend to be reduced. The melt viscosity at 100°C is measured by a B-type rotational viscometer.

[0050] The glass transition temperature (Tg) of the (meth)acrylic resin (A) is preferably 20° C. or lower, more preferably −70° C. to 0° C., even more preferably −68 to −10° C., and particularly preferably −65 to −30° C. If the glass transition temperature is too low, the cohesive strength of the pressure-sensitive adhesive layer decreases, and the adhesive properties before irradiation with active energy rays tend to decrease; if the glass transition temperature is too high, the melt viscosity of the active energy ray-curable peel-type pressure-sensitive adhesive composition tends to increase, and the coatability tends to decrease.

[0051] The glass transition temperature is calculated by the following Fox formula. TIFF0007643150000001.tif37150Tg: Glass transition temperature of polymer (K) Tga: Glass transition temperature (K) of homopolymer of monomer A Wa: Weight fraction of monomer A Tgb: Glass transition temperature (K) of the homopolymer of monomer B Wb: Weight fraction of monomer B Tgn: Glass transition temperature (K) of homopolymer of monomer N Wn: Weight fraction of monomer N (Wa+Wb+···+Wn=1)

[0052] That is, it is a value calculated by applying the glass transition temperature and weight fraction of each of the monomers constituting the acrylic resin to the Fox formula when the polymer is made into a homopolymer. The glass transition temperature of a homopolymer of the monomers constituting the acrylic resin is usually measured by a differential scanning calorimeter (DSC), and can be measured by a method in accordance with JIS K7121-1987 or JIS K6240.

[0053] The refractive index of the (meth)acrylic resin (A) is usually 1.440 to 1.600. It is preferable to make the difference in refractive index between the (meth)acrylic resin (A) and the member to be laminated small, since this reduces optical loss at the interface between the members.

[0054] The refractive index is a value measured by measuring the thin film of the (meth)acrylic resin (A) using a refractive index measuring device (Abbe Refractometer 1T manufactured by Atago Co., Ltd.) at 23°C using NaD rays.

[0055] The solvent content in the (meth)acrylic resin (A) is preferably less than 1% by weight, more preferably 0.5% by weight or less, and particularly preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer will decrease, and the adhesive performance and reworkability before curing with active energy rays will tend to decrease. The content is measured by gas chromatography-mass spectrometry (GC-MS).

[0056] [Active energy ray-curable compound (B)] The requirement (α) of the present invention is that the active energy ray-curable compound (B) contains a urethane (meth)acrylate compound (b). The active energy ray-curable compound (B) used in the present invention contains a urethane (meth)acrylate-based compound (b), and may also contain a monofunctional (meth)acrylate, a polyfunctional (meth)acrylate, or the like.

[0057] The urethane (meth)acrylate compound (b) may be a urethane (meth)acrylate compound (b-1) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1) and a polyvalent isocyanate compound (b2); a urethane (meth)acrylate compound (b-2) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), and a polyol compound (b3); or a urethane (meth)acrylate compound (b-3) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), a monofunctional alcohol (b4), and, if necessary, a polyol compound (b3).

[0058] Among these, in the present invention, in terms of compatibility with the (meth)acrylic resin (A) and releasability and contamination resistance after irradiation with active energy rays, a urethane (meth)acrylate compound (b-2) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1) and a polyvalent isocyanate compound (b2) or a urethane (meth)acrylate compound (b-3) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), a monofunctional alcohol (b4), and, if necessary, a polyol compound (b3) is preferred. In the present invention, the urethane (meth)acrylate compound (b) may be used alone or in combination of two or more kinds.

[0059] For example, when the hydroxyl group-containing (meth)acrylate compound (b1) has one hydroxyl group, the polyvalent isocyanate compound (b2) has two isocyanate groups, the polyol compound (b3) has two hydroxyl groups, and the monofunctional alcohol (b4) has one hydroxyl group, the reaction molar ratio of the hydroxyl group-containing (meth)acrylate compound (b1) to the polyvalent isocyanate compound (b2) and polyol compound (b3) when synthesizing the urethane (meth)acrylate compound (b-2) is usually about 2:1:2 in molar ratio of polyvalent isocyanate compound (b2):polyol compound (b3):hydroxyl group-containing (meth)acrylate compound (b1). Furthermore, when a urethane (meth)acrylate compound (b-3) is used, the reaction molar ratio of the hydroxyl group-containing (meth)acrylate compound (b1) to the polyvalent isocyanate compound (b2) and the monofunctional alcohol (b4) is usually about 1:1:1 in terms of the molar ratio of polyvalent isocyanate compound (b2): hydroxyl group-containing (meth)acrylate compound (b1): monofunctional alcohol (b4), and when a polyol is used in combination, the molar ratio of polyvalent isocyanate compound (b2): polyol compound (b3): ​​hydroxyl group-containing (meth)acrylate compound (b1): monofunctional alcohol (b4) is usually about 2:1:1:1.

[0060] The hydroxyl group-containing (meth)acrylate compound (b1) is preferably one having one hydroxyl group, and examples thereof include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 2-hydroxy-3-(meth)acrylate. Examples of the hydroxyl group-containing (meth)acrylate compounds include those containing one ethylenically unsaturated group, such as aryloyloxypropyl (meth)acrylate; those containing two ethylenically unsaturated groups, such as glycerin di(meth)acrylate and 2-hydroxy-3-acryloyloxypropyl methacrylate; and those containing three or more ethylenically unsaturated groups, such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate. These hydroxyl group-containing (meth)acrylate compounds (b1) can be used alone or in combination of two or more.

[0061] Of the hydroxyl group-containing (meth)acrylate compounds (b1), those containing three or more ethylenically unsaturated groups are preferred because of their excellent reactivity and versatility, and pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate are particularly preferred.

[0062] Examples of the polyisocyanate compound (b2) include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; and aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate. cyanates; alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; or isocyanurates or polymeric compounds of these polyisocyanates, allophanate polyisocyanates, biuret polyisocyanates, and water-dispersible polyisocyanates (for example, "AQUANATE 100," "AQUANATE 110," "AQUANATE 200," and "AQUANATE 210," manufactured by Nippon Polyurethane Industry Co., Ltd.).

[0063] Among these, in terms of excellent reactivity and versatility, aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate, and alicyclic diisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate are preferred, with isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, and hexamethylene diisocyanate being particularly preferred, and isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate being even more preferred.

[0064] The polyol compound (b3) may be any compound containing two or more hydroxyl groups, and examples thereof include aliphatic polyols, alicyclic polyols, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, (meth)acrylic polyols, polysiloxane polyols, etc. These may be used alone or in combination of two or more.

[0065] Examples of the aliphatic polyols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylenediol, 1,3-tetramethylenediol, 2-methyl-1,3-trimethylenediol, 1,5-pentamethylenediol, 1, Examples include aliphatic alcohols containing two hydroxyl groups such as 6-hexamethylenediol, 3-methyl-1,5-pentamethylenediol, 2,4-diethyl-1,5-pentamethylenediol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols such as xylitol and sorbitol; and aliphatic alcohols containing three or more hydroxyl groups such as glycerin, trimethylolpropane, and trimethylolethane.

[0066] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyldimethanol, hydrogenated bisphenols such as hydrogenated bisphenol A, and tricyclodecane dimethanol.

[0067] Examples of the polyether polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol, as well as random or block copolymers of these polyalkylene glycols.

[0068] Examples of the polyester polyol include condensation polymers of polyhydric alcohols and polycarboxylic acids; ring-opening polymers of cyclic esters (lactones); and reaction products of three components: polyhydric alcohols, polycarboxylic acids, and cyclic esters.

[0069] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol). Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid. Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.

[0070] Examples of the polycarbonate polyol include a reaction product of a polyhydric alcohol with phosgene, and a ring-opening polymerization product of a cyclic carbonate ester (such as an alkylene carbonate). Examples of the polyhydric alcohol include the polyhydric alcohols exemplified in the description of the polyester polyol, and examples of the alkylene carbonate include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate. The polycarbonate polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.

[0071] The polyolefin polyols include those having a homopolymer or copolymer of ethylene, propylene, butene, or the like as a saturated hydrocarbon skeleton and having hydroxyl groups at the molecular terminals.

[0072] The polybutadiene polyol may be a polybutadiene polyol having a butadiene copolymer as a hydrocarbon skeleton and hydroxyl groups at its molecular terminals. The polybutadiene polyol may be a hydrogenated polybutadiene polyol in which all or part of the ethylenically unsaturated groups contained in the polybutadiene polyol structure have been hydrogenated.

[0073] The polyisoprene-based polyol may be a polyisoprene polyol having an isoprene copolymer as a hydrocarbon backbone and hydroxyl groups at the molecular terminals. The polyisoprene-based polyol may be a hydrogenated polyisoprene polyol in which all or part of the ethylenically unsaturated groups contained in the polyisoprene-based polyol structure have been hydrogenated.

[0074] The (meth)acrylic polyols include those having at least two hydroxyl groups in the molecule of a (meth)acrylic acid ester polymer or copolymer, and examples of such (meth)acrylic acid esters include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate.

[0075] Examples of the polysiloxane polyol include dimethylpolysiloxane polyol and methylphenylpolysiloxane polyol.

[0076] Among these, aliphatic polyols and alicyclic polyols are preferably used from the viewpoint of cost, and polyester polyols, polyether polyols and polycarbonate polyols are preferably used from the viewpoint of versatility.

[0077] The weight-average molecular weight of the polyol compound (b3) is preferably 60 to 10,000, particularly preferably 100 to 5,000, and even more preferably 200 to 4,000. If the weight-average molecular weight of the polyol compound (b3) is too large, the resulting urethane (meth)acrylate compound (b) and the (meth)acrylic resin (A) tend to be less uniformly mixed, which tends to reduce the releasability after irradiation with active energy rays. On the other hand, if the weight-average molecular weight of the polyol compound (b3) is too small, cracks tend to be more likely to occur in the pressure-sensitive adhesive layer after irradiation with active energy rays.

[0078] The monofunctional alcohol (b4) is not particularly limited, but examples thereof include alcohols containing a linear or branched alkyl group having 1 to 36 carbon atoms, aromatic ring-containing alcohols, alicyclic group-containing alcohols, and heterocycle-containing alcohols, and from the viewpoint of versatility, alcohols containing a linear or branched alkyl group having 1 to 36 carbon atoms are preferred, and alcohols containing a linear or branched alkyl group having 4 to 18 carbon atoms are more preferred. These may be used alone or in combination of two or more.

[0079] The urethane (meth)acrylate compound (b) can be produced by reacting the above components by known reaction means. An example is shown below. (1) To obtain a urethane (meth)acrylate compound (b-1) A method of subjecting the hydroxyl group-containing (meth)acrylate compound (b1) to a urethane reaction with a polyisocyanate compound (b2). (2) To obtain urethane (meth)acrylate compound (b-2) A method of subjecting the hydroxyl group-containing (meth)acrylate compound (b1), a polyisocyanate compound (b2), and a polyol compound (b3) to a urethane reaction. (3) To obtain urethane (meth)acrylate compound (b-3) A method of subjecting the hydroxyl group-containing (meth)acrylate compound (b1), the polyisocyanate compound (b2), the polyol compound (b3), and further the monofunctional alcohol (b4) to a urethane reaction. The urethane-forming reaction can be carried out by charging the above components into a reactor all at once or separately and carrying out the urethane-forming reaction by a known reaction means. When producing a urethane (meth)acrylate compound (b-2) or a urethane (meth)acrylate compound (b-3), a method of reacting a polyol compound (b3) with a polyvalent isocyanate compound (b2) in advance to obtain a reaction product, and then reacting the resulting product with a hydroxyl group-containing (meth)acrylate compound (b1) or a monofunctional alcohol (b4) is useful in terms of the stability of the urethane-forming reaction and the reduction of by-products.

[0080] In the reaction between the hydroxyl group-containing (meth)acrylate compound (b1) and the polyvalent isocyanate compound (b2), it is preferable to use a reaction catalyst to promote the reaction. Examples of such reaction catalysts include organometallic compounds such as dibutyltin dilaurate, trimethyltin hydroxide, and tetra-n-butyltin; metal salts such as zinc octenoate, tin octenoate, tin octoate, cobalt naphthenate, stannous chloride, and stannic chloride; amine catalysts such as triethylamine, benzyldiethylamine, 1,4-diazabicyclo[2,2,2]octane, 1,8-diazabicyclo[5,4,0]undecene, N,N,N',N'-tetramethyl-1,3-butanediamine, and N-ethylmorpholine; bismuth nitrate, bismuth bromide, bismuth iodide, and bismuth sulfide; and dibutyltin. Examples of suitable catalysts include organic bismuth compounds such as thyl bismuth dilaurate and dioctyl bismuth dilaurate; bismuth 2-ethylhexanoate, bismuth naphthenate, bismuth isodecanoate, bismuth neodecanoate, bismuth laurate, bismuth maleate, bismuth stearate, bismuth oleate, bismuth linoleate, bismuth acetate, bismuth bisneodecanoate, bismuth disalicylate, and bismuth digallate; zirconium catalysts such as inorganic zirconium, organic zirconium, and simple zirconium; and combinations of two or more catalysts such as zinc 2-ethylhexanoate / zirconium tetraacetylacetonate. Among these, dibutyltin dilaurate and organic bismuth compounds are preferred. These catalysts can be used singly or in combination.

[0081] In the urethanization reaction, organic solvents that do not have a functional group that reacts with an isocyanate group, such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, and aromatics such as toluene and xylene, can be used.

[0082] The reaction temperature for the urethane-forming reaction is usually 30 to 90° C., preferably 40 to 80° C., and the reaction time is usually 2 to 10 hours, preferably 3 to 8 hours.

[0083] The urethane-forming reaction is terminated when the content of residual isocyanate groups in the reaction system reaches 0.5% by weight or less, thereby obtaining the urethane (meth)acrylate compound (b).

[0084] The (meth)acryloyl group concentration of the urethane (meth)acrylate compound (b) obtained in this manner is 0.5 mmol / g or more, preferably 1.0 to 35 mmol / g, more preferably 1.5 to 20 mmol / g, and particularly preferably 2.0 to 15 mmol / g. By setting the (meth)acryloyl group concentration of the urethane (meth)acrylate compound (b) to be within the above range, excellent releasability after irradiation with active energy rays can be achieved.

[0085] In addition, the urethane (meth)acrylate compound (b) preferably has three or more ethylenically unsaturated groups from the viewpoint of releasability after irradiation with active energy rays. If the number of ethylenically unsaturated groups is too small, sufficient crosslinking density cannot be obtained, and the releasability after irradiation with active energy rays tends to decrease.

[0086] The weight-average molecular weight of the urethane (meth)acrylate compound (b) is usually 200 to 10,000, preferably 400 to 5,000, and more preferably 600 to 4,000. If the weight-average molecular weight is too large, the active energy ray-curable compound (B) and the (meth)acrylic resin (A) will not be uniformly mixed, and the adhesive properties before and after active energy ray irradiation will tend to deteriorate. If the weight-average molecular weight is too small, the cohesive force of the adhesive layer will tend to decrease, and the adhesive properties will tend to deteriorate.

[0087] The weight-average molecular weight is the weight-average molecular weight converted to standard polystyrene molecular weight, and is measured using a high-performance liquid chromatograph (Waters, "ACQUITY APC System") with four columns arranged in series: one ACQUITY APCXT450, one ACQUITY APCXT200, and two ACQUITY APCXT45.

[0088] The viscosity of the urethane (meth)acrylate compound (b) used in the present invention at 60°C is preferably 50 to 10,000 mPa·s, more preferably 100 to 7,000 mPa·s, and particularly preferably 200 to 4,000. If the viscosity is too low, the cohesive force tends to decrease, and if it is too high, the coatability tends to decrease. The viscosity can be measured using an E-type viscometer.

[0089] Furthermore, the active energy ray-curable compound (B) may also contain a monofunctional (meth)acrylate or a polyfunctional (meth)acrylate.

[0090] [Monofunctional (meth)acrylate] Examples of such monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, acrylonitrile, 2-methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-phenoxy-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, glycerin mono(meth)acrylate, glycidyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyl (meth)acrylate. Peroxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)-methyl (meth)acrylate, cyclohexanespiro-2-(1,3-dioxolan-4-yl)-methyl (meth)acrylate, 3-ethyl-3-oxetanylmethyl (meth)acrylate, γ-butyrolactone (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, n-stearyl (meth)acrylate, benzyl (meth)acrylate, phenol ethylene oxide modified (n=2) (meth)acrylate, nonylphenol propylene oxide modified (n=2).5) (Meth)acrylate monomers such as half (meth)acrylates of phthalic acid derivatives, such as 2-(meth)acryloyloxyethyl acid phosphate and 2-(meth)acryloyloxy-2-hydroxypropyl phthalate, furfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, carbitol (meth)acrylate, benzyl (meth)acrylate, butoxyethyl (meth)acrylate, allyl (meth)acrylate, (meth)acryloylmorpholine, and polyoxyethylene secondary alkyl ether acrylate, 2-hydroxyethyl acrylamide, N-methylol (meth)acrylamide, N-vinylpyrrolidone, 2-vinylpyridine, and vinyl acetate.

[0091] [Multifunctional (meth)acrylate] Examples of polyfunctional (meth)acrylates include bifunctional (meth)acrylates and trifunctional or higher acrylates. Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-modified bisphenol A di(meth)acrylate, propylene oxide-modified bisphenol A di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, Examples of the diglycidyl acrylate include acrylate, ethoxylated cyclohexanedimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, phthalic acid diglycidyl ester di(meth)acrylate, hydroxypivalic acid-modified neopentyl glycol di(meth)acrylate, and isocyanuric acid ethylene oxide-modified diacrylate.

[0092] Examples of trifunctional or higher functional acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerin polyglycidyl ether poly(meth)acrylate, isocyanuric acid ethylene oxide modified triacrylate, caprolactone modified dipentaerythritol penta(meth)acrylate, caprylic / capric tri ... Examples of the ethylene oxide-modified dipentaerythritol hexa(meth)acrylate include caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, and ethoxylated 15-glycerin triacrylate.

[0093] Furthermore, Michael adducts of acrylic acid or 2-acryloyloxyethyl dicarboxylic acid monoesters can also be used in combination, and examples of such Michael adducts of acrylic acid include (meth)acrylic acid dimer, (meth)acrylic acid trimer, and (meth)acrylic acid tetramer. The 2-acryloyloxyethyl dicarboxylic acid monoester is a carboxylic acid having a specific substituent, and examples thereof include 2-acryloyloxyethyl succinic acid monoester, 2-methacryloyloxyethyl succinic acid monoester, 2-acryloyloxyethyl phthalic acid monoester, 2-methacryloyloxyethyl phthalic acid monoester, 2-acryloyloxyethyl hexahydrophthalic acid monoester, 2-methacryloyloxyethyl hexahydrophthalic acid monoester, etc. Furthermore, other examples include oligoester acrylates, etc. These monofunctional (meth)acrylates and polyfunctional (meth)acrylates can be used alone or in combination of two or more.

[0094] The content of the urethane (meth)acrylate compound (b) in the active energy ray-curable compound (B) is 50% by weight or more, preferably 80% by weight or more, with the upper limit being 100% by weight. If the content is too low, the peelability and stain resistance after active energy ray irradiation tend to decrease.

[0095] The solvent content in the active energy ray-curable compound (B) is preferably less than 1% by weight, more preferably 0.5% by weight or less, and particularly preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer will decrease, and the adhesive performance and reworkability before curing with active energy rays will tend to decrease. The content is measured by gas chromatography-mass spectrometry (GC-MS).

[0096] [Active energy ray-curable composition (X)] In the active energy ray-curable composition (X) of the present invention, the content of the active energy ray-curable compound (B) is 10 to 200 parts by weight per 100 parts by weight of the (meth)acrylic resin (A), preferably 30 to 150 parts by weight, and particularly preferably 50 to 120 parts by weight. If the content of the active energy ray-curable compound (B) is too low, the peelability after irradiation with active energy rays tends to be easily reduced, while if it is too high, the cohesive strength of the pressure-sensitive adhesive layer tends to be reduced, and the adhesive properties before and after irradiation with active energy rays tend to be reduced.

[0097] The requirement (β) of the present invention is that the solvent content in the active energy ray-curable composition (X) is less than 1% by weight, preferably 0.5% by weight or less, and particularly preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer will decrease, and the adhesive performance and reworkability before curing with active energy rays will tend to decrease. The content is measured by gas chromatography-mass spectrometry (GC-MS).

[0098] The requirement (γ) of the present invention is that the content of the thermal polymerization initiator in the active energy ray-curable composition (X) is less than 200 ppm. The content of such a thermal polymerization initiator is less than 200 ppm, preferably less than 100 ppm, and more preferably less than 50 ppm. If this content is too high, the thermal stability tends to decrease. This content can be reduced by reducing the amount of the thermal polymerization initiator in the (meth)acrylic resin (A).

[0099] The amount of thermal polymerization initiator is measured by liquid chromatography mass spectrometry (LC-MS).

[0100] Furthermore, the requirement (ω) of the present invention is that the melt viscosity of the active energy ray-curable composition (X) at 100°C is 120 Pa s or less, and preferably less than 100 Pa s. If the melt viscosity is much higher than the above range, the coatability tends to be significantly reduced. The melt viscosity of the active energy ray-curable composition (X) at 100° C. is measured using a B-type rotational viscometer.

[0101] [Crosslinker (C)] The active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention may further contain a crosslinking agent (C) in addition to the active energy ray-curable composition (X). Examples of the crosslinking agent (C) include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, and amine-based crosslinking agents. Among these, it is preferable to use an isocyanate-based crosslinking agent in terms of improving the adhesion of the release-type pressure-sensitive adhesive sheet to the substrate sheet and reactivity with the (meth)acrylic resin (A). Furthermore, these crosslinking agents (C) may be used alone or in combination of two or more.

[0102] Examples of the isocyanate crosslinking agent include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, adducts of these polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret and isocyanurate forms of these polyisocyanate compounds. Among these, in terms of chemical resistance and reactivity with functional groups, the isocyanurate of hexamethylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, adduct of 2,6-tolylene diisocyanate and trimethylolpropane, isocyanurates of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, and adduct of tetramethylxylylene diisocyanate and trimethylolpropane are preferred.

[0103] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.

[0104] Examples of the aziridine crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).

[0105] Examples of the oxazoline-based crosslinking agent include 2,2'-bis(2-oxazoline), 1,2-bis(2-oxazolin-2-yl)ethane, 1,4-bis(2-oxazolin-2-yl)butane, 1,8-bis(2-oxazolin-2-yl)butane, 1,4-bis(2-oxazolin-2-yl)cyclohexane, 1,2-bis(2-oxazolin-2-yl)benzene, and 1,3-bis(2-oxazolin-2-yl) Examples include bisoxazoline compounds containing aliphatic or aromatic groups such as benzene, and polymers of one or more addition-polymerizable oxazolines such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.

[0106] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, and melamine resins.

[0107] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.

[0108] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.

[0109] The content of the crosslinking agent (C) is usually preferably 0.1 to 30 parts by weight, particularly preferably 0.2 to 20 parts by weight, and even more preferably 0.3 to 15 parts by weight, per 100 parts by weight of the (meth)acrylic resin (A). If the amount of crosslinking agent (C) is too small, the cohesive strength of the adhesive layer tends to decrease, and the adhesive properties tend to decrease. If the amount of crosslinking agent (C) is too large, the adhesive strength before irradiation with active energy rays tends to decrease, and lifting or peeling tends to occur between the adhesive layer and the workpiece.

[0110] [Photopolymerization initiator (D)] The photopolymerization initiator (D) used in the present invention may be any one that generates radicals by the action of light. When the (meth)acrylic resin contains a photocrosslinkable monomer, the (meth)acrylic resin does not need to contain a photopolymerization initiator. Examples of such photopolymerization initiators (D) include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one. acetophenones such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer; benzoins such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide benzophenones such as 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, and (4-benzoylbenzyl)trimethylammonium chloride; 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1 thioxanthones such as 2-chloro-4-propoxythioxanthone and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; and acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.Among these, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, etc. are preferred because they do not sublimate even when heated and are stable. These photopolymerization initiators (D) can be used alone or in combination of two or more.

[0111] Examples of auxiliary agents for the photopolymerization initiator (D) include triethanolamine, triisopropanolamine, and 4,4'-dimethylaminobenzophenone (Michler's ketone). It is also possible to use in combination with 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, etc. These auxiliary agents can also be used alone or in combination of two or more.

[0112] The content of the photopolymerization initiator (D) is preferably 0.1 to 20 parts by weight, particularly preferably 0.5 to 15 parts by weight, and especially preferably 1 to 10 parts by weight, relative to 100 parts by weight of the active energy ray-curable compound (B). If the content of the photopolymerization initiator (D) is too low, the peelability after irradiation with active energy rays tends to be easily reduced, while if it is too high, the contamination resistance of the workpiece after irradiation with active energy rays tends to be reduced.

[0113] [Other ingredients] The active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention may further contain small amounts of additives such as monofunctional monomers, antistatic agents, antioxidants, plasticizers, fillers, pigments, diluents, antioxidants, UV absorbers, and UV stabilizers, provided that the effects of the present invention are not impaired. These additives may be used alone or in combination of two or more. Antioxidants are particularly effective in maintaining the stability of the pressure-sensitive adhesive layer. When an antioxidant is added, its content is not particularly limited, but is preferably 0.01 to 5 wt % relative to the active energy ray-curable release-type pressure-sensitive adhesive composition. In addition to the above additives, the active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention may also contain small amounts of impurities contained in the raw materials used to produce the components of the active energy ray-curable release-type pressure-sensitive adhesive composition.

[0114] Furthermore, the active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention preferably does not contain a tackifying resin such as a terpene-based resin, a rosin-based resin, a chroman-based resin, a phenol-based resin, a styrene-based resin, or a petroleum-based resin, since the contamination resistance of the workpiece becomes low after irradiation with active energy rays.

[0115] [Active energy ray-curable peelable pressure-sensitive adhesive composition] Thus, the active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention is obtained by mixing the (meth)acrylic resin (A), the active energy ray-curable composition (X) containing the active energy ray-curable compound (B), and, if necessary, optional components such as the crosslinking agent (C), the photopolymerization initiator (D), the ethylenically unsaturated compound, and other components.

[0116] The solvent content in the active energy ray-curable peel-type pressure-sensitive adhesive composition is less than 1.5% by weight, and preferably less than 1% by weight. If this value is too high, a large amount of solvent will remain in the adhesive layer, which will tend to reduce the cohesive strength and adhesive properties. The solvent content is measured by gas chromatography-mass spectrometry (GC-MS).

[0117] The active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention is crosslinked by the above-mentioned crosslinking agent (C) and is suitably used as the pressure-sensitive adhesive layer of a peel-type pressure-sensitive adhesive sheet. After this peel-type pressure-sensitive adhesive sheet is attached to a workpiece, the active energy ray-curable composition (X) polymerizes and the pressure-sensitive adhesive layer hardens when irradiated with active energy rays, resulting in a decrease in adhesive strength, thereby exhibiting peelability. Taking advantage of this property, the composition is used to temporarily protect the surface of various workpieces when processing the workpieces. The peelable pressure-sensitive adhesive sheet will be described below.

[0118] Examples of workpieces that can be protected by the peelable pressure-sensitive adhesive sheet include semiconductor wafers, printed circuit boards, processed glass products, metal plates, and plastic plates.

[0119] The release-type pressure-sensitive adhesive sheet typically comprises a substrate sheet, a pressure-sensitive adhesive layer comprising the active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention, and a release film. To prepare such a release-type pressure-sensitive adhesive sheet, the active energy ray-curable release-type pressure-sensitive adhesive composition of the present invention is first applied directly to a release film or a substrate sheet, either as is or after adjusting the concentration with an appropriate organic solvent. The composition is then dried, for example, by heat treatment at 80 to 105°C for 0.5 to 10 minutes, and then attached to a substrate sheet or a release film to obtain a release-type pressure-sensitive adhesive sheet. Furthermore, to balance the adhesive properties, further aging may be performed after drying.

[0120] Examples of the substrate sheet include sheets made of at least one synthetic resin selected from the group consisting of polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; and polyimide; and woven and nonwoven fabrics made of metal foils such as aluminum, copper, and iron, paper such as fine paper and glassine paper, glass fiber, natural fibers, synthetic fibers, etc. These substrate sheets can be used as a single layer or as a multi-layered body in which two or more types are laminated together. Among these, sheets made of synthetic resins are preferred from the viewpoint of weight reduction, etc.

[0121] Furthermore, as the release film, for example, various synthetic resin sheets, paper, woven fabrics, nonwoven fabrics, etc. exemplified above as the base sheet can be used which have been subjected to a release treatment.

[0122] The method for applying the active energy ray-curable release-type pressure-sensitive adhesive composition is not particularly limited as long as it is a common application method, and examples thereof include roll coating, die coating, gravure coating, comma coating, and screen printing.

[0123] The thickness of the pressure-sensitive adhesive layer in the above-mentioned peelable pressure-sensitive adhesive sheet is usually preferably 1 to 200 μm, and more preferably 10 to 100 μm.

[0124] As the active energy rays, generally, light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, neutron beams, etc. can be used. However, it is advantageous to use ultraviolet rays in terms of curing speed, ease of availability of irradiation equipment, cost, etc.

[0125] The cumulative dose of ultraviolet light is usually 50 to 3000 mJ / cm2, and preferably 100 to 1000 mJ / cm2. The irradiation time varies depending on the type of light source, the distance between the light source and the pressure-sensitive adhesive layer, the thickness of the pressure-sensitive adhesive layer, and other conditions, but is usually several seconds, and in some cases may be as short as less than one second.

[0126] The adhesive strength of the above-mentioned peel-type pressure-sensitive adhesive sheet varies depending on the type of base sheet, the type of workpiece, etc., but the 180-degree peel strength before irradiation with active energy rays is usually 1 N / 25 mm or more, and preferably 3 N / 25 mm or more.

[0127] The peel strength of the above-mentioned peelable pressure-sensitive adhesive sheet after irradiation with active energy rays is usually lower than the peel strength before irradiation with active energy rays. The 180-degree peel strength of the above-mentioned peel-type pressure-sensitive adhesive sheet after irradiation with active energy rays is usually 1 N / 25 mm or less, and preferably 0.5 N / 25 mm or less.

[0128] A peelable adhesive sheet using the active energy ray-curable peelable adhesive composition of the present invention as an adhesive layer can be easily peeled off from a workpiece by laminating it to the workpiece to temporarily protect the surface of the workpiece and then irradiating it with active energy rays, which hardens the adhesive layer and reduces the adhesive strength. [Example]

[0129] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. Note that "%" and "parts" below are based on weight.

[0130] <Preparation of (meth)acrylic resin (A) solution> [Acrylic resin (A-1)] A reactor equipped with a temperature controller, a thermometer, a stirrer, a dropping funnel, and a reflux condenser was charged with 50 parts of methyl ethyl ketone and 0.042 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (ADVN (thermal polymerization initiator)) as a polymerization catalyst, and the temperature was raised with stirring. When the internal temperature stabilized at 78°C, a mixture of 65.45 parts of 2-ethylhexyl acrylate (a1), 25.45 parts of 2-hydroxyethyl methacrylate (a2), 9.10 parts of vinyl acetate, 0.083 parts of ADVN, and 3.3 parts of methyl ethyl ketone as copolymerization components was added dropwise over 2 hours, and the reaction was carried out under reflux. Next, 3 hours after the start of the reaction, a solution of 3.3 parts of methyl ethyl ketone and 0.083 parts of ADVN was added, and 4.5 hours after the start of the reaction, a solution of 3.3 parts of ethyl acetate and 0.083 parts of ADVN was added. The reaction was terminated 7 hours after the start of the reaction, yielding an acrylic resin (A-1) solution with a glass transition temperature of -51.4°C, a resin content of 62.2%, a viscosity of 1500 mPa·s (25°C), and a weight-average molecular weight Mw of 122,000. Next, the obtained acrylic resin (A-1) solution was poured into a flask equipped with a reflux liquid withdrawal tube, and the solution was heated at 90°C for 1 hour, and then the pressure was reduced to 10 kPa and the mixture was maintained at 90°C for 3 hours to distill off the solvent, thereby obtaining acrylic resin (A-1) (melt viscosity at 100°C: 120 Pa·s).

[0131] [Acrylic resin (A'-1)] Acrylic resin (A'-1) was obtained in the same manner as above, except that the amount of ADVN (thermal polymerization initiator) added to acrylic resin (A-1) was increased.

[0132] [Acrylic resin (A'-2)] A reactor equipped with a temperature controller, a thermometer, a stirrer, a dropping funnel, and a reflux condenser was charged with 75 parts of methyl ethyl ketone and 0.042 parts of ADVN as a polymerization catalyst, and the temperature was raised with stirring. When the internal temperature stabilized at 78°C, a mixture of 52 parts of n-butyl acrylate (a1), 20 parts of methyl methacrylate, 28 parts of 2-hydroxyethyl methacrylate (a2), 0.083 parts of ADVN, and 3.3 parts of methyl ethyl ketone as copolymerization components was added dropwise over 2 hours, and the reaction was carried out under reflux. Next, 3 hours after the start of the reaction, a solution of 3.3 parts of methyl ethyl ketone and 0.042 parts of ADVN was added, and 4.5 hours after the start of the reaction, a solution of 3.3 parts of methyl ethyl ketone and 0.042 parts of ADVN was added. The reaction was completed 9 hours after the start of the reaction, yielding an acrylic resin (A'-2) solution with a glass transition temperature of -23.7°C, a resin content of 58.5%, a viscosity of 11,500 mPa·s (25°C), and a weight-average molecular weight Mw of 231,000. Next, the obtained acrylic resin (A'-2) solution was poured into a flask equipped with a reflux liquid extraction tube, and the solution was heated at 90°C for 1 hour, then the pressure was reduced to 10 kPa and the mixture was maintained at 90°C for 3 hours to distill off the solvent, thereby obtaining an acrylic resin (A'-2) with a melt viscosity of 2000 Pa·s or more.

[0133] [Table 1]

[0134] * 2EHA: 2-ethylhexyl acrylate BA: n-butyl acrylate MMA: Methyl methacrylate HEA: 2-hydroxyethyl acrylate VAc: vinyl acetate

[0135] <Preparation of active energy ray-curable compound (B)> [Urethane acrylate (B-1)] In a four-neck flask equipped with a temperature controller, thermometer, stirrer, water-cooled condenser, and nitrogen gas inlet, 9.4 parts of isophorone diisocyanate (isocyanate group content: 37.8%) (manufactured by Evonik Japan) and Sannix PP-2000 43.3 parts (hydroxyl value: 54.9 mg KOH / g) (manufactured by Sanyo Chemical Industries, Ltd.), 47.3 parts of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value: 51 mg KOH / g), 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate groups reached 0.3% or less, yielding a mixture of urethane acrylate (B) (10 ethylenically unsaturated groups, weight average molecular weight 7,500, acryloyl group concentration 4.73 mmol / g).

[0136] [Urethane acrylate (B-2)] Dicyclohexylmethane 4,4'-diisocyanate (isocyanate group content: 32.0%) (manufactured by Evonik Japan) was placed in a four-neck flask equipped with a temperature controller, thermometer, stirrer, water-cooled condenser, and nitrogen gas inlet. 25.8 parts of ammonium nitrate, 46.2 parts of pentaerythritol triacrylate and pentaerythritol tetraacrylate (hydroxyl value: 119.1 mg KOH / g), 28.0 parts of Fine Oxocol 180T (hydroxyl value: 203.0 mg KOH / g) (Nissan Chemical Co., Ltd.), 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60 ° C. The reaction was terminated when the residual isocyanate group was 0.3% or less, and a mixture of urethane acrylate (B) (3 ethylenically unsaturated groups, weight average molecular weight 1,400, acryloyl group concentration 4.87 mmol / g) was obtained.

[0137] [Polyfunctional (meth)acrylate (B-3)] Trimethylolpropane triacrylate (Toa Gosei Chemical Co., Ltd.: Aronix M-309)

[0138] [Preparation of active energy ray-curable composition (X)] The acrylic resin (A) and the urethane acrylate (b) were mixed (requirement (α)) in the amounts shown in Table 2 to obtain active energy ray-curable compositions (X).

[0139] [Requirement (β): Solvent content] The solvent content in the obtained active energy ray-curable composition (X) was measured. The results are shown in Table 2.

[0140] [Requirement (γ): Content of thermal polymerization initiator] The amount of the thermal polymerization initiator in the obtained active energy ray-curable composition (X) was measured using LC-MS. The detection limit of the thermal polymerization initiator was 5 ppm.

[0141] [Requirement (ω): Melt viscosity] The obtained active energy ray-curable composition (X) was allowed to stand at 100° C. for 24 hours, and then the viscosity at 100° C. was measured using a B-type rotational viscometer and evaluated according to the following evaluation criteria. ○: Melt viscosity 120 Pa·s or less ×: Melt viscosity greater than 120 Pa·s

[0142] (thermal stability) The obtained active energy ray-curable composition (X) was allowed to stand at 100° C. for 24 hours, and then the appearance was visually inspected and evaluated according to the following evaluation criteria. ◯: Neither thickening nor gelation was observed. ×: Thickening or gelation was observed.

[0143] [Table 2]

[0144] <Examples 1 to 6, Comparative Examples 1 to 3> The active energy ray-curable composition (X) prepared above and the following components were blended in the amounts shown in Table 3 to obtain an active energy ray-curable peel-type pressure-sensitive adhesive composition, and a peel-type pressure-sensitive adhesive sheet was produced.

[0145] [Crosslinking agent (C)] Isocyanate-based crosslinking agent (C-1): Trimethylolpropane adduct of tolylene diisocyanate (Tosoh Corporation: Coronate L-55E)

[0146] [Photopolymerization initiator (D)] Photopolymerization initiator (D-1): 2-dimethylamine-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butanone (OMNIRAD379 manufactured by IGM Resins)

[0147] [Preparation of peelable adhesive sheet] The obtained active energy ray-curable peel-type pressure-sensitive adhesive composition was blended with the components listed in Table 3 and heated to 100°C. The mixture was then applied with an applicator to a polyethylene terephthalate film (film thickness 38 μm) (manufactured by Toray Industries, Inc., "T60 Lumirror") as a substrate sheet, dried at 100°C for 2 minutes, cooled to room temperature, and then attached to a release film (manufactured by Mitsui Chemicals Tocello, Inc., "SP-PET3801-BU") and aged at 40°C for 7 days to obtain a peel-type pressure-sensitive adhesive sheet (adhesive layer thickness 25 μm). The peelable pressure-sensitive adhesive sheets obtained were subjected to the following evaluations, and the results are shown in Table 3.

[0148] (Coatability) The appearance of the resulting peelable pressure-sensitive adhesive sheet was visually observed and evaluated according to the following criteria. 〇: The coating is uniform with no unevenness or streaks. ×: The coating film is uneven and has streaks.

[0149] (Adhesive strength before exposure to active energy rays) A 25mm x 100mm test piece was prepared from the peel-off adhesive sheet obtained above, and after peeling off the release film, the piece was pressed onto a stainless steel plate (SUS304BA plate) by rolling a 2kg rubber roller back and forth twice in an atmosphere of 23°C and 50% relative humidity. After leaving the sheet to stand in the same atmosphere for 30 minutes, the 180-degree peel strength (N / 25mm) was measured at a peel speed of 300mm / min and evaluated according to the following criteria. 〇:5N / 25mm or more △: 1N / 25mm or more, less than 5N / 25mm ×: Less than 1N / 25mm

[0150] (Adhesive strength after exposure to active energy rays) A 25mm x 100mm test piece was prepared from the resulting peel-type adhesive sheet. After peeling off the release film, the piece was pressed against a stainless steel plate (SUS304BA plate) at 23°C and 50% relative humidity by rolling a 2kg rubber roller back and forth twice. After leaving the sheet at 23°C and 50% relative humidity for 30 minutes, it was irradiated with ultraviolet light (cumulative exposure dose 250mJ / cm2) from a height of 18cm using an 80W high-pressure mercury lamp at a conveyor speed of 51.0m / min. After leaving the sheet at 23°C and 50% relative humidity for 30 minutes, the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min. ○: Less than 0.1N / 25mm △: 0.1N / 25mm or more, less than 1.0N / 25mm ×:1.0N / 25mm or more

[0151] [Table 3]

[0152] *Comparative Example 1: The adhesive could not be evaluated because it gelled when heated and could not be applied. Comparative Example 2: Unevenness and streaks occurred on the coating, making it impossible to evaluate adhesive strength.

[0153] In Example 1, the active energy ray-curable composition (X) had excellent thermal stability, the active energy ray-curable peel-type pressure-sensitive adhesive composition had excellent coatability, and the adhesive strength before and after active energy ray irradiation was also excellent. On the other hand, in Comparative Example 1, in which the amount of thermal polymerization initiator remaining in the active energy ray-curable peel-type pressure-sensitive adhesive composition exceeded the predetermined amount, gelation was observed upon heating, indicating poor thermal stability, and the evaluation was discontinued. In addition, in Comparative Example 2, in which the melt viscosity of the active energy ray-curable peel-type pressure-sensitive adhesive composition exceeded 200 Pa·s, the viscosity during coating was too high, causing unevenness and streaks in the coating film, resulting in poor coatability, and the evaluation was discontinued. Furthermore, Comparative Example 3, which did not contain urethane (meth)acrylate as the active energy ray-curable compound (B), was excellent in thermal stability and melt viscosity, but was poor in adhesive strength before active energy ray curing.

[0154] The above results show that when an active energy ray-curable peel-type pressure-sensitive adhesive composition containing an active energy ray-curable compound that contains a urethane (meth)acrylate (b) (requirement (α)) and an active energy ray-curable composition (X) with an extremely low solvent content (requirement (β)) is used as a peel-type pressure-sensitive adhesive sheet, by satisfying the following: the amount of thermal polymerization initiator in the active energy ray-curable composition (X) is less than 200 ppm (requirement (γ)), ​​and the viscosity of the active energy ray-curable composition (X) at 100°C is 120 Pa s or less (requirement (ω)), a pressure-sensitive adhesive composition that has excellent coatability and, as a peel-type pressure-sensitive adhesive sheet, has excellent adhesive strength before and after irradiation with active energy rays and excellent contamination resistance after peeling can be obtained. [Industrial Applicability]

[0155] The active energy ray-curable peel-type pressure-sensitive adhesive composition of the present invention can be suitably used as a temporary surface-protective pressure-sensitive adhesive sheet (peel-type pressure-sensitive adhesive sheet) when processing semiconductor wafers, printed circuit boards, processed glass products, metal plates, plastic plates, etc.

Claims

1. The composition (X) contains an active energy ray-curable composition (X) that contains a (meth)acrylic resin (A) and an active energy ray-curable compound (B), The (meth)acrylic resin (A) has a weight average molecular weight of 50,000 or more and 1,000,000 or less and contains a structural unit derived from a functional group-containing monomer, An active energy ray-curable peel-type pressure-sensitive adhesive composition, characterized in that the active energy ray-curable composition (X) satisfies all of the following requirements (α) to (ω): Requirement (α): The active energy ray-curable compound (B) contains a urethane (meth)acrylate-based compound (b). Requirement (β): The solvent content in the active energy ray-curable composition (X) is less than 1% by weight. Requirement (γ): The content of the thermal polymerization initiator in the active energy ray-curable composition (X) is less than 200 ppm. Requirement (ω): The melt viscosity of the active energy ray-curable composition (X) at 100° C. is 120 Pa·s or less.

2. 2. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the functional group-containing monomer is at least one selected from the group consisting of hydroxyl group-containing monomers and carboxyl group-containing monomers.

3. 3. The active energy ray-curable peelable pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylic resin (A) has a glass transition temperature of −30° C. or lower.

4. The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of claims 1 to 3, further comprising a crosslinking agent (C).

5. The active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of claims 1 to 4, further comprising a photopolymerization initiator (D).

6. A peelable pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer in which the active energy ray-curable peelable pressure-sensitive adhesive composition according to any one of claims 1 to 5 is crosslinked.

Citation Information

Patent Citations

  • Pressure sensitive adhesive sheet for use in semiconductor wafer processing and its manufacturing method

    JP2004269796A

  • Emulsion type adhesive composition, adhesive sheet, and method of removing the adhesive sheet

    JP2012001615A

  • Ultraviolet-curing hot-melt adhesive, and adhesive sheet and adhesive label using the same

    JP2012021127A

  • Adhesive tape for semiconductor wafer surface protection

    JP2013201263A

  • Adhesive composition for touch panels, adhesive film, and touch panel

    JP2013543912A